Imbalanced Datasets in the Generation of Fuzzy Classification Systems - An Investigation using a Multiobjective Evolutionary Algorithm based on Decomposition - Cardenas, EH (2016)
The first and third author acknowledge the Peruvian agencies FONDECYT and CONCYTEC for the support. The second author acknowledges the Brazilian agencies CAPES and FAPESP for the support